Problems & Prospects of Nomadic Shepherds: Exploring the challenges and opportunities of the nomadic shepherd community (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Preamble The Nomadic Shepherds community lives in open lands, forests and villages. This community is seen in Karnataka, Maharashtra, Uttar Pradesh, Punjab, Rajasthan and Madhya Pradesh. Nomadic shepherds rearing sheep, goat, cow, horse…etc. Their history traced back to the early periods in the Indian history.Sheep with multi fact utility i. e of meat, milk, skin and manure….etc form an important component of nomadic shepherd’s economy, particularly in the arid, semi-arid and mountainous areas of the country. It provides a dependable source of income to shepherds (small and marginal sheep rearing) through sale of work and animals.These men take care of livestock throughout the year leading a semi-nomadic life style (batch wise-adjustment in going coming) moving with the grazing animals from one place to another, while their family stays back at home.Nomadic Shepherds are” Group of a people or a tribe that move from place to place, usually seasonally and often following a traditional route or circuit according to the state of the pastorate or food supply .The main objectives of this study are 1.To understand the nomadic life style or cultural educational problems 2.To understand the problems of migration marketing to sell their animals, products…..etc.